Ritual di Bawah Pohon Asam Mbah Gosang di Pasar Peterongan Semarang - Siti Nur Asiyah; Mudjahirin Thohir; Af'idatul Lathifah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
Along with the development of modern times, society maintains its tradition as a unique cultural identity, including the phenomenon of rituals that take place under a large tamarind tree which is believed to be the firing of a sacred figure named Mbah Gosang, located in the middle of an urban area, precisely at Peterongan Semarang Market. The focus of the discussion which is the main objective of this research is to interpret the ritual meanings express in the ritual implementation. This research uses the theory of symbolic interactionism in explaining ritual phenomena, which in implication refers to social actions carried out by individuals in representing cultural meanings and symbols around them. The method used in this study is in the form of ethnographic methods, while the source of research data is obtained from participatory observation, in-depth interviews, and literature review. The informants consisted of the caretaker and Mbah Gosang pilgrim who had been directly involved in the implementation of ritual traditions. Based on the results of the study, the phenomenon of rituals carried out under the Mbah Gosang tamarind tree has two forms of cultural traditions in the form of a pilgrimage ritual and suronan ritual which in essence involves Mbah Gosang as an intermediary for prayer or tawassul to God. The series of ritual processions has their own symbolic meaning. Generally, people who carry out these rituals have the motivation to improve the economy, look for prosperity in life, and look for clues in dealing with life problems. The function of the ritual itself is as a form of respect for ancestors, cultural inheritance, forms of effort, reminders of death, and means of social integration, while the purpose of the ritual is to draw closer to God Almighty.